Degradation and transport pathways of steroid hormones from human and animal waste - Yang, Yun-Ya, author; Borch, Thomas, advisor; Davis, J. G. (Jessica Gwyn), 1962-, committee member; Barbarick, Kenneth Arthur, committee member; Goodridge, Lawrence David, 1971-., committee member (Colorado State University. Libraries, 2010)
Steroid hormones have been widely detected in various environmental matrices, including soils, groundwater, surface water, and sediments. Agricultural operations where manure and biosolids are applied as fertilizers and soil amendments are potential sources of steroid hormones to the environment. The aim of this research is to assess the potential for surface runoff and to elucidate biodegradation pathways of steroid hormones from human and animal waste, respectively. A field-scale study was conducted to assess the potential for runoff of seventeen different steroid hormones from an agricultural field applied with biosolids at an agronomic rate and the major runoff mechanisms. Steroid hormones were present in runoff from the biosolids amended agricultural field, and high concentrations of androgens and progesterone were observed in the runoff even after multiple rainfall events and up to one month after biosolids application. The observed correlation between rainfall amount and hormone mass flux suggests that intense rainfall promotes hormone runoff. Hormones were found to be transported primarily in the aqueous phase or by particles smaller than 0.7 µm. The potential for biodegradation of testosterone, 17β-estradiol and progesterone by swine (Sus scrofa) manure-borne bacteria was examined, and the impact of different environmental factors on testosterone degradation kinetics was determined. Testosterone, 17β-estradiol and progesterone were rapidly degraded under aerobic conditions, and testosterone has the potential for degradation by manure-borne bacteria under a wide range of environmentally relevant conditions. Finally, a study was conducted to enrich manure-borne bacteria capable of testosterone degradation and to elucidate the testosterone mineralization pathway by the enriched bacteria under aerobic conditions. Six DNA sequences of bacteria from the Proteobacteria phylum were identified in a testosterone-degrading enriched culture, suggesting that Proteobacteria may play an important environmental role in the degradation of testosterone and other similar structural compounds. The microbial enrichment caused 48% of the added 14C-testosterone to be mineralized to 14CO2 within 8 days of incubation. The findings in this dissertation contribute important information that will help improve our current understanding of the environmental fate of steroid hormones as well as assist in the development of best management practices for biosolids and manure.
Keywords: sewage purification; transport; steroid hormones; biosolids; manure; degradation; Steroid hormones -- Biodegradation; Steroid hormones -- Environmental aspects; Sewage sludge; Testosterone -- Biodegradation